Use of Technology in Scuba Diving. Dive Computers: Ensuring Continuous Safety and Peak Experience - Djozic, Amar (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management